Reconfigurable meander line dipole antenna based on two rectangular defected ground structure - Khaled B. Suleiman; Abobaker Albishti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In this study, a reconfigurable double-sided meander line dipole antenna (RMLA) incorporated with a tapered balun was developed to function at 0.9 GHz, 2.4 GHz, and 3.7 GHz. Furthermore, the suggests antenna functions at three modes at different frequency bands with pattern reconfiguration. Two positive-intrinsic-negative (PIN) diodes were embedded in the two rectangular defected ground structures to accomplish frequency and pattern reconfigurability. With excellent impedance matching, the return loss in each of these bands keeps beneath -10 dB. The suggested antenna was designed using computer simulation technology 2020 and constructed on a FR-4 substrate with a thickness of 1.6 mm, and dielectric constant of 4.3 mm respectively. Additionally, for antenna size reduction, meander line technique was embedded. The fundamental working mechanism of this reconfigurable antenna is accomplished by changing the status of a radio frequency (RF) switches, which is carried out in on or off mode. For the three resonant bands, the suggested antenna has a voltage standing waves ratio (VSWR) < 2. Up to 80%, the suggested structure radiation efficiency and gain (1−2.8) dBi are calculated. The suggested antenna is well suitable for global system mobile, wireless fidelity (WiFi) and C-band applications because of its notable features of high efficiency, good gain and frequency reconfigurability.